Inibição da atividade catalítica da proteína dissulfeto isomerase por tempol - Santos, Gérsika Bitencourt (2011)
Protein disulfide isomerase (PDI, EC 5.3.4.1) is an ubiquitously expressed enzyme that catalyses the rearrangement of disulfide bonds in target proteins. Previous studies suggest that PDI, which is a chaperone involved in protein trafficking and translocates to the cell surface, may regulate the phagocytic NADPH oxidase complex (Nox2). This study examines whether the nitroxide 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinyloxy (Tempol) inhibits the regulatory activity of PDI interconnected to Nox2 in inflammatory neutrophils. Phorbol-triggered superoxide anion release was correlated with the PDI reductase activity detected in neutrophils, as determined by oxygen consumption and cleavage of a fluorescent probe, respectively. Both events were significantly inhibited in a concentration-dependent manner when neutrophils were pre-treated with Tempol, which has an ED50 of 45 M. To substantiate that Tempol’s action on PDI activity is related to Nox2 downregulation, assays with the known PDI inhibitors bacitracin and dithionitrobenzoic acid were performed to confirm their ability to decrease the neutrophil respiratory burst. This study shows that Tempol’s inhibition of Nox2 activity is correlated with decreased PDI reductase activity at the neutrophil cellular membrane, suggesting a close association between the enzymes of activated phagocytes and pointing to a novel anti-inflammatory mechanism for Tempol.